TI_GERICHTE 72.2004.49 vom 2. September 2004 , furto tentato e consumato di chili 1'000 di canapa sequestrati dagli inquirenti - TI Tribunale d'appello (2004)
furto tentato e consumato di chili 1'000 di canapa sequestrati dagli inquirenti